2006
DOI: 10.1093/ndt/gfl399
|View full text |Cite
|
Sign up to set email alerts
|

Use of renal risk drugs in hospitalized patients with impaired renal function--an underestimated problem?

Abstract: Among patients admitted to general hospitals, a considerable proportion had renal impairment. In patients with reduced renal function, renal risk drugs were widely used and often in combination. DRPs were frequently associated with the use of renal risk drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
79
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 14 publications
9
79
2
1
Order By: Relevance
“…In patients with kidney insufficiency, as the frequency of inappropriate drug use increases, the course of disease worsens. 8 Inappropriate drug use results in a 40% increase in the mortality of the patients with insufficient renal function. 17 The present study has revealed that inappropriate drug use is quite common in the CKD population.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In patients with kidney insufficiency, as the frequency of inappropriate drug use increases, the course of disease worsens. 8 Inappropriate drug use results in a 40% increase in the mortality of the patients with insufficient renal function. 17 The present study has revealed that inappropriate drug use is quite common in the CKD population.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of inappropriate drug use found in this study is higher compared to the findings of other studies. 8,12,16,21,22 The negative effects of nonsteroid anti-inflammatory drugs on renal functions have been known. In our study, 44.3% of CKD patients were aged 65 and over, and the rate of inappropriate drug use was higher in this group compared to the rest of the population (86.6% vs. 75.7%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations